A Preliminary Examination of a Vocal Generalized Conditioned Reinforcer. (5th November 2015) - Helton, Maria R.; Ivy, Jonathan W.
Abstract : Generalized conditioned reinforcers (GCRs) in the form of tokens are commonly used in behavioral treatment. However, it is possible for non‐tangible consequences to also function as GCRs. For example, a vocal stimulus (e.g., good job) associated with completion of a work task, access to preferred actives, and peer interaction could function as a GCR. The purpose of this study was to examine the effects of pairing a vocal stimulus with multiple edible reinforcers on the Frequency math problem completion. The results suggest that a vocal statement paired with an array of four back‐up reinforcer functioned as a GCR for completing math problems for two typically developing children identified as having minor deficits in math skills. Copyright © 2015 John Wiley & Sons, Ltd.